Two sides of data protection: Examining the complex and political nature to the personal data transfers between the European Union and the United States - Lunden, Miska (My University, 2022)
This thesis investigates the complexity and the political aspects of the data protection. This thesis is viewed from the perspective of international transfers of personal data between the European Union and the United States. These two parties were chosen because of the special role each one has - the US in the cloud storages and the EU in the privacy regulation sphere. The thesis follows legal dogmatic methodology based on legal and doctrinal research materials with a focus on the importance of well- functioning data protection legislation by placing an interest towards technology-based approach rather than political. The thesis contains in-depth analysis on the history of EU’s data protection legislation and to events that have influenced it trying to answer the question what is wrong and why. Furthermore, the thesis attempts to resolve underlying problems with the current data protection legislation and analyse whether technological innovations could be used to our benefit. The thesis reaches the result that the possibility of having political sway in the data protection legislation has an impact and does not resolve the underlying problem of trust. Furthermore, technological innovations such as Fully Homomorphic Encryption could be used to resolve, at least partially, the problems faced in data protection. I reached the conclusion that if the EU chooses not to go with technology based problem-solving methods, adequacy decisions should be approved by the European Data Protection instead of the European Commission.
Keywords: Data protection, Privacy, GDPR